Self-Consciousness and Different Ways of Measuring Stress - Huić, Aleksandra (Array, 2008)
Research that tried to link self-consciousness with levels of stress is inconclusive. It was hypothesized that individuals high in private self-consciousness should in a way be protected from the negative influence of stress (e. g. they will notice body tension sooner than those low in private self-consiousness and will be able cope with it sooner). However, studies that showed that a higher degree of self-consciousness is correlated with negative and more intense emotional reactions have put this hypothesis into question.According to some authors (Trapnell and Campbell, 1999) psychological interpretation of results depends upon the reason someone is focusing onto him/herself. They divided self-consciousness in the distinct motivational tendencies: (1) rumination – neurotic focus characterized by constant dwelling upon past events and (2) reflection – a need to understand oneself and seek answers to spiritual questions. The purpose of the study was to try to explain inconsistencies in research findings. Firstly, we examined individual differences in private self-consciousness in relation to different ways of stress measurement in order to check whether the study results depend on the method used. Secondly, we put the findings in the context of motivational tendencies of self-consciousness and checked whether the results are consistent with Trapnell and Campbell's explanation.